An improved model for describing the net carrier recombination rate in semiconductor devices - Inche Ibrahim, Mohd Lukman; Anvar A., Zakhidov (Springer Nature, 2022)
Carrier recombination is a process that significantly influences the performance of semiconductor devices such as solar cells, photodiodes, and light-emitting diodes (LEDs). Therefore, a model that can accurately describe and quantify the net carrier recombination rate in semiconductor devices is important in order to further improve the performance of relevant semiconductor devices. The conventional model for describing the net carrier recombination rate is derived based on the condition that there is no electric current in the considered semiconductor, which is true only when the semiconductor is not part of a device, and hence, is not connected to an external circuit. The conventional model is adopted and used for describing the net carrier recombination rate in semiconductors that are part of devices (i.e., in semiconductor devices). In this paper, we derive and propose a new model for describing the net carrier recombination rate in semiconductor devices. The newly proposed model is an improvement to the currently used model by considering the fact that electric currents can flow in the semiconducting materials of semiconductor devices. We employ organic solar cells (OSCs) to validate the proposed recombination model and show that the proposed model can be crucial for modeling OSCs. Since the proposed recombination model is derived for general semiconductor devices, we expect that the use of the proposed model can also be crucial for modeling and analyzing the performance of other semiconductor devices, particularly optoelectronic devices such as LEDs and perovskite solar cells.